2017
DOI: 10.1080/09546634.2017.1329503
|View full text |Cite
|
Sign up to set email alerts
|

Real world prescription trends of methotrexate for psoriasis in Argentina: results of a national survey

Abstract: A wide heterogeneity in the prescribing profile of MTX for the treatment of psoriasis was observed among Argentinean dermatologists. Suboptimal MTX use was identified in the majority of the prescribers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Mazzuoccoloa et al reported suboptimal use of MTX by 76% of dermatologists in Argentina. 32 Comparable results were found in Holland, where 11% of dermatologists were not well-informed about guidelines. Although 80% of Dutch dermatologists use MTX in clinical practice, only 52% adhere to treatment guidelines when prescribing it.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Mazzuoccoloa et al reported suboptimal use of MTX by 76% of dermatologists in Argentina. 32 Comparable results were found in Holland, where 11% of dermatologists were not well-informed about guidelines. Although 80% of Dutch dermatologists use MTX in clinical practice, only 52% adhere to treatment guidelines when prescribing it.…”
Section: Discussionmentioning
confidence: 92%
“…Mazzuoccoloa et al conducted a survey on the use of MTX for Pso treatment among Argentinian dermatologists (n = 221). 32 They found that two-thirds of dermatologists included the PPD test and/or a chest X-Ray in their pretreatment work-up. Half of them expected a clinically significant response between weeks 4 and 6 of MTX treatment, 44% between weeks 8 and 12, and 6% after 12 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Surveys of international practice have highlighted heterogeneity in the prescription of methotrexate for this indication. 4,5 Herein, we evaluate the modalities of methotrexate prescription for moderate to severe psoriasis by dermatologists in France.…”
mentioning
confidence: 99%